Primary results from IMpassion131, a double-blind, placebo-controlled, randomised phase III trial of first-line paclitaxel with or without atezolizumab for unresectable locally advanced/metastatic triple-negative breast cancer - Miles, David W.; Gligorov, J.; André, F.; Cameron, D.; Schneeweiss, Andreas; Barrios, C.; Xu, B.; Wardley, A.; Kaen, D.; Andrade, L.; Semiglazov, V.; Reinisch, M.; et al. (Annals of oncology, 2021)
Background - In the phase III IMpassion130 trial, combining atezolizumab with first-line nanoparticle albumin-bound-paclitaxel for advanced triple-negative breast cancer (aTNBC) showed a statistically significant progression-free survival (PFS) benefit in the intention-to-treat (ITT) and programmed death-ligand 1 (PD-L1)-positive populations, and a clinically meaningful overall survival (OS) effect in PD-L1-positive aTNBC. The phase III KEYNOTE-355 trial adding pembrolizumab to chemotherapy for aTNBC showed similar PFS effects. IMpassion131 evaluated first-line atezolizumab-paclitaxel in aTNBC. - Patients and methods - Eligible patients [no prior systemic therapy or ≥12 months since (neo)adjuvant chemotherapy] were randomised 2:1 to atezolizumab 840 mg or placebo (days 1, 15), both with paclitaxel 90 mg/m2 (days 1, 8, 15), every 28 days until disease progression or unacceptable toxicity. Stratification factors were tumour PD-L1 status, prior taxane, liver metastases and geographical region. The primary endpoint was investigator-assessed PFS, tested hierarchically first in the PD-L1-positive [immune cell expression ≥1%, VENTANA PD-L1 (SP142) assay] population, and then in the ITT population. OS was a secondary endpoint. - Results - Of 651 randomised patients, 45% had PD-L1-positive aTNBC. At the primary PFS analysis, adding atezolizumab to paclitaxel did not improve investigator-assessed PFS in the PD-L1-positive population [hazard ratio (HR) 0.82, 95% confidence interval (CI) 0.60-1.12; P = 0.20; median PFS 6.0 months with atezolizumab-paclitaxel versus 5.7 months with placebo-paclitaxel]. In the PD-L1-positive population, atezolizumab-paclitaxel was associated with more favourable unconfirmed best overall response rate (63% versus 55% with placebo-paclitaxel) and median duration of response (7.2 versus 5.5 months, respectively). Final OS results showed no difference between arms (HR 1.11, 95% CI 0.76-1.64; median 22.1 months with atezolizumab-paclitaxel versus 28.3 months with placebo-paclitaxel in the PD-L1-positive population). Results in the ITT population were consistent with the PD-L1-positive population. The safety profile was consistent with known effects of each study drug. - Conclusion - Combining atezolizumab with paclitaxel did not improve PFS or OS versus paclitaxel alone. - ClinicalTrials.gov - NCT03125902.
Gesehen am 03.11.2021